All about my selfie - Freeman, Shannon (Shannon Ford) (Freeman, Shannon (Shannon Ford). Summit Middle School, 2015)
When Emma Swanson begins posting more selfies and garnering more attention, her relationship with her best friends Mai and Carson suffers. Then she becomes a victim of an Internet prank and Emma needs her friends more than ever.